Gnoseological problems in Andean thought. An ethnographic and hermeneutical inquiry - Flores Gutiérrez, María (2021)
In order to investigate the conception of the Andean people about gnoseological problems, conceived from these categories: possibility of knowledge, elements that intervene in knowledge, process of knowledge, telos of knowledge and conception of truth.  An ethnographic-hermeneutical method was used in the town of Rosaspata, Ayacucho District, Huamanga Province, Peru. The key informants were the yachaq (people who preserve the knowledge of the original peoples) authorities and elderly residents. It was evidenced that Andean people conceive knowledge as a process that begins in the sensory phase with the rikuy (see), the uyary (listen), accompanied by the ruray (praxis). It passes to the second phase of rational operations such as yachay (knowing), musyay (intuiting), and hamutay (reflection), in which true knowledge (chiqap) is acquired, as a correspondence between the knowable object and its representation. The telos of knowledge is the allin kawsay, or the harmony between man and nature, and between men. It is concluded that Andean people identify the elements of knowledge: the riqsina (knowable object) and the riqsiq (knowing subject) in a relationship of mutual belonging, but not opposition, which is typical of Western culture. This finding is relevant because after five centuries of westernization, of economic, social and cultural colonialism, Andean people have not renounced to their cultural roots and horizontal conception of nature, as a fundamental part of the knowledge of the world.